Somatic GNAQ mutation in different structures of port‐wine macrocheilia. (14th August 2018) - Ma, G.; Yu, Z.; Liu, F.; Wang, L.; Yu, W.; Zhu, J.; Gu, H.; Liu, Y.; Cai, R.; Lin, X.
Summary: Background: Port‐wine macrocheilia (PWM) involves a congenital, progressive capillary malformation that results in soft‐tissue hypertrophy in the lips. Its aetiology has not yet been fully elucidated. Objectives: To investigate frequencies of GNAQ mutation in different tissues from patients with PWM, including skin, mucosa, gland and muscle, using samples obtained during cheiloplasty. Methods: Targeted next‐generation sequencing of GNAQ was designed and performed to assess DNA extracted from 80 different affected tissues from 20 patients with PWM. Results: The GNAQ R183Q mutation was not detected in gland samples but was found in 90%, 95% and 95% of the skin, mucosal and muscle samples, respectively. The lowest levels of mutations were found in the glands ( P < 0·001 vs. skin, mucosa and muscle), and levels were second lowest in the skin ( P = 0·023 vs. mucosa; P = 0·012 vs. muscle). The mutation frequencies in mucosa and muscle were the highest and showed no statistically significant difference ( P = 0·92). Conclusions: In patients with PWM, GNAQ was mutated in all tissues except for glands. PWM is congenital, and all tissue layers exhibit primary hypertrophy rather than acquired or partially related hypertrophy. Given the advantages of mucosal biopsy, including practicality, lack of scarring and rapid healing, GNAQ mutation in the lip mucosa may be a useful predictor for early‐stage PWM in patients with port‐wine stains affecting the lips. Abstract : What's already known about this topic? Port‐wine stains are caused by a somatic activating mutation in GNAQ, a protein that mediates signals between G‐protein‐coupled receptors and downstream effectors. There is limited information regarding the genetic study of patients with port‐wine macrocheilia. What does this study add? Our data suggest different GNAQ mutation frequencies in the structures of port‐wine macrocheilia. What is the translational message? Our results suggest that GNAQ mutations in mucosa may be a predictor for early‐stage port‐wine macrocheilia. Respond to this article Plain language summary available online